2023
DOI: 10.3390/jcm12134351
|View full text |Cite
|
Sign up to set email alerts
|

Nanofat in Plastic Reconstructive, Regenerative, and Aesthetic Surgery: A Review of Advancements in Face-Focused Applications

Simone La Padula,
Martina Ponzo,
Mariagiovanna Lombardi
et al.

Abstract: Nanofat is a relatively novel technique in fat grafting that has gained significant interest in the fields of regenerative medicine, aesthetic and translational research. It involves the extraction of autologous fat from a patient, which is then transformed into “nanofat”, consisting of small fat particles with a diameter of less than 0.1 mm and containing high concentrations of stem cells and growth factors. This article focuses on the use of nanofat in facial rejuvenation and its potential for lipomodelling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 74 publications
(232 reference statements)
0
12
0
Order By: Relevance
“…Recent research has demonstrated that the mechanical shear stress imposed on the fat during the preparation of nanofat generates an upregulation of signaling pathways to enhance stem cells' regenerative capacity. 18,32 These complex pathways result in enhanced tissue remodeling with collagen deposition and skin elasticity, dermal thickening, angiogenesis, and a decrease in melanin synthesis. 18 Studies suggest that the multiple cell types in the stromal vascular fraction may work in combination synergistically as the culprit to trigger the rejuvenative capacity of the stem cell and the tissue itself.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent research has demonstrated that the mechanical shear stress imposed on the fat during the preparation of nanofat generates an upregulation of signaling pathways to enhance stem cells' regenerative capacity. 18,32 These complex pathways result in enhanced tissue remodeling with collagen deposition and skin elasticity, dermal thickening, angiogenesis, and a decrease in melanin synthesis. 18 Studies suggest that the multiple cell types in the stromal vascular fraction may work in combination synergistically as the culprit to trigger the rejuvenative capacity of the stem cell and the tissue itself.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…18,32 These complex pathways result in enhanced tissue remodeling with collagen deposition and skin elasticity, dermal thickening, angiogenesis, and a decrease in melanin synthesis. 18 Studies suggest that the multiple cell types in the stromal vascular fraction may work in combination synergistically as the culprit to trigger the rejuvenative capacity of the stem cell and the tissue itself. 18,32 Many tissue engineering strategies seek to combine burst kinetics with prolonged release for pharmacologically consistent delivery of drugs and growth factors including VEGF, PDGF, and FGF for engineering-inducible scaffolds for cell transfer and neovascularization.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 3 more Smart Citations